Petrography, compositional characteristics and stable isotope geochemistry of the ewekoro formation from ibese corehole, eastern Dahomey basin, southwestern Nigeria (2016)
"Subsurface samples of the predominantly carbonate Ewekoro Formation, obtained from Ibese core hole within the Dahomey basin were used in this study. Investigations entail petrographic, elemental composition as well as stable isotopes (carbon and oxygen) geochemistry in order to deduce the different microfacies and depositional environment. Petrographic study reveals the presence of dolomite, biomicrite, sandy biomicrite, and biosparite facies. Preserved pore types such as; intercrystaline, moldic and vuggy pores were observed as predominant conduits for fluids. The major element oxides ranges are; CaO (39.79 - 53.98wt.%), SiO2 (1.29-25.37 wt. %) Al2O3 (0.43-3.77 wt. %), K2O(0.04-0.27wt. %), Fe2O3 (0.74-2.35 wt. %), and Na2O (<0.01-0.05 wt. %). Cross correlation of the major oxide contents shows that Al2O3, K2O, Na2O, TiO2, Fe2O3 and P2O5 are associated with aluminosilicates and their low concentrations indicates that the basin was free of suspended clays and other aluminosilicates materials during carbonate sedimentation. The relatively high concentration of SiO2 and its interrelationship with other major oxides, suggests SiO2 has strictly influenced the sedimentation of the carbonate hence would have been contributed as free silica, probably from beaches and not as aluminosilicates. The Mn/Sr ratio reveals an influence of diagenesis on the mineralogy of the carbonates. The Mg/Ca ratio ranges from 0.02 and 0.1 (av. 0.04), with an outlier value of 0.1, indicating a strong diagenetic influence and the precipitation of dolomite in the mixing zone The isotopic composition of ᵹ13C (-1.9%o to 0.79%o) shows a discrepancy from modern carbonate sediments. The average estimated formational temperature of the limestone is 32.5°C. The ᵹ13O versus ᵹ18O bivariate diagram indicates that the limestone is predominantly average marine limestone with chalk and late cement. The values of depositional setting (Z), estimated from ᵹ13O and ᵹ18O composition support a diagenetic influence on the Ewekoro Formation. The U/Th ratios (-0.25 to 2.3; av. 1.2) and Ce anomaly (0.70 - 0.94, av. 0.85) indicate a predominantly oxygenated environment with little fluctuation in bottom water oxygen level. "